Kejahatan Pengedaran Uang Kertas Palsu menurut Pasal 245 KUHP: Studi Kasus Putusan Perkara No. 695k/Pid/2009 - Manulu, Karto (Advokasi Hukum & Demokrasi (AHD), 2024)
The circulation of counterfeit money is not a simple, independent event, but is the result of various factors which coincidentally become a phenomenon that is very detrimental to all parties involved and also detrimental to the country in improving development. The circulation of counterfeit money is not a simple, independent event, but is the result of various factors which coincidentally become a phenomenon that is very detrimental to all parties involved and also detrimental to the country in improving development. In connection with the above, Law no. 1 of 1946 Articles 9 and 10 and also uses the mandate of the Criminal Code, especially Article 245 regarding the circulation of counterfeit banknotes in Indonesia. The basis for issuing the law is because money is a legal means of payment and is issued by Bank Indonesia and money as a means of exchange that has a fixed price can help a person fulfill various needs and achieve life goals that are considered important. However, in practice, the circulation of counterfeit money increases every year.